IMPACT OF LESION COMPLEXITY ON PCI SUCCESS IN LAD DISEASE: A RETROSPECTIVE STUDY - DURRANI , T; SYEDA , A; HUSSAIN , I; KHAN , P; QAYYUM , K; DURRANI , H (Biological and Clinical Sciences Research Journal, 2024)
Coronary artery disease (CAD) involving the left anterior descending (LAD) artery is a major cause of morbidity and mortality globally. The prognosis of patients with coronary artery disease depends on the extent of at-risk myocardium. LAD comparatively supplies a large percentage of the left ventricle compared to RCA or LCX. The principal indication of percutaneous coronary intervention is to improve the quality of life in patients with angina refractory to medications. There are many advancements in PCI techniques for better management of challenging lesions due to physiological, anatomical, or functional difficulties. Some of the complex lesions include ostial lesions, bifurcating lesions, calcified lesions, and chronic total occlusions. However, as lesion complexity plays a significant role in procedural success and long-term outcomes, complex lesions are often associated with increased rates of restenosis, adverse events, and procedural challenges Objective: This study aims to evaluate the impact of lesion complexity on PCI success in patients with LAD disease. Methods: This retrospective cohort study was conducted from January 1, 2021, to December 31, 2023, at a tertiary cardiovascular center. A total of 216 participants who had PCI to LAD lesions done were included. Lesion complexity was assessed using the SYNTAX score and categorised into low, intermediate, and high complexity groups. The primary outcome was restenosis at 12 months, defined as ≥50% luminal narrowing in patients requiring repeat angiography due to any indication. Secondary outcomes included procedural success, major adverse cardiac events (MACE), and rates of stent thrombosis. Data were analysed using SPSS version 24.0, with statistical significance set at p < 0.05. Results: Among the 216 participants, 72% were male, and the mean age was 61.4 ± 9.8 years. Restenosis occurred in 13.9% of participants, with higher rates observed in patients with high-complexity lesions (24.5%) compared to low-complexity lesions (7.7%) (p = 0.02). Procedural success was achieved in 92.6% of cases, though it decreased with increasing lesion complexity (97.8% for low, 93.4% for intermediate, and 85.7% for high-complexity groups). MACE occurred in 4.6% of participants, with stent thrombosis noted in 2.7%. Conclusion: Lesion complexity significantly influences PCI success and restenosis rates in LAD disease. Patients with higher complexity lesions experience worse outcomes, necessitating individualised treatment strategies to optimise procedural success.